EFEKTIVITAS PEMBELAJARAN MATEMATIKA BILINGUAL PADA MATERI PERKALIAN DI SD NEGERI 27 KOTA SORONG MELALUI MEDIA PERMAINAN WORDWALL: EFFECTIVENESS OF BILINGUAL MATHEMATICS LEARNING ON MULTIPLICATION MATERIAL IN STATE ELEMENTARY SCHOOL 27 SORONG CITY THROUGH WORDWALL GAME MEDIA - Trisnawati, Nika Fetria; Sipahelut, Ania; Fauzi, Azra; Yuliani, Nova (KAMBIK: Journal of Mathematics Education, 2025)
Effective mathematics learning requires methods and media that are engaging for students. The use of digital media, such as wordwall can increase student engagement in understanding multiplication concepts, especially in a bilingual learning environment. This study aims to evaluate the effectiveness of bilingual mathematics learning on multiplication material at SD Negeri 27, Sorong City, by utilizing wordwall game media. This study used a quantitative descriptive approach through a pre-test and post-test involving 23 third-grade students. The results showed an increase in the average student score from 64.35 in the pre-test to 83.26 in the post-test, with an N-Gain value of 0.6036, which is classified as a moderate increase. In addition to improving the understanding of multiplication concepts, the use of wordwall also motivates students to be more active in the learning process. The bilingual approach that combines Indonesian and English also provides benefits in developing students' language skills. Thus, it is concluded that Wordwall media is effective in improving learning outcomes, creating an interactive and interesting learning atmosphere, and supporting the improvement of the quality of mathematics learning at the elementary school level.